New material for treating mining area composite pollutants through electrochemical process, preparation method and application

By developing molybdenum modified tricarbon dioxide polymer as electrode surface coating, the problem of difficult to efficiently deal with composite pollutants in the mining area in electrochemical processes is solved, and the effect of efficient removal of heavy metal complexes is achieved, which has important environmental protection and economic value.

CN119774719AActive Publication Date: 2025-04-08SOUTH CHINA NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510273320.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently treat heavy metal complexes in composite pollutants in mining areas, especially in electrochemical processes, and lacks suitable anode materials to effectively break and recover heavy metal ions.

Method used

A molybdenum modified tricarbon dioxide polymer (Fe/Mo-p(C3O2)x-300) was developed, and the electrochemical degradation of raw materials such as malonic acid, acetic anhydride, ammonium molybdate and iron sulfate were used to form a dark red solid material and coated on the electrode surface to improve the efficiency of the electrochemical degradation process.

Benefits of technology

This material significantly improves the removal efficiency of heavy metals in composite pollutants in the electrochemical degradation process, can achieve a removal rate of 100% in 45 minutes, and the removal efficiency of heavy metals in mine groundwater reaches 80.1% in 120 minutes of treatment time, significantly reducing the cost of wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774719A_ABST
    Figure CN119774719A_ABST
Patent Text Reader

Abstract

The invention relates to a novel material for treating mining area composite pollutants through an electrochemical process and a preparation method and application thereof, and belongs to the technical field of novel materials and application thereof.The novel material for treating mining area composite pollutants through the electrochemical process is prepared through the following steps that 1, malonic acid, acetic anhydride, ammonium molybdate and ferric sulfate are added into a reaction container, mixed, heated and dissolved, and a mixture is obtained; continuously raising the temperature to 135 to 145 DEG C, and keeping the temperature for 3 to 6 hours; (2) after the reaction is finished, dropwise adding diethyl ether to precipitate a product, carrying out suction filtration, washing with diethyl ether, and collecting the precipitated product; (3) performing vacuum drying on the precipitation product to obtain a solid product; and (4) heating the solid product to 300 DEG C in a nitrogen atmosphere, carrying out heat treatment for 0.5-2 hours at the temperature, and cooling to room temperature to obtain a dark red solid material, namely the new material, which is used as an anode coating material, has the removal efficiency of heavy metals in composite pollutants reaching 100% in 45 minutes in an electrochemical degradation process, and has the removal efficiency of heavy metals in composite pollutants reaching 100% in 120 minutes when the actual mine underground water is treated for 120 minutes. And the removal efficiency reaches 80.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials and their application, and specifically relates to a new material for treating composite pollutants in mining areas by electrochemical process, and a preparation method and application thereof. Background Art

[0002] With the continuous acceleration of the global economy and industrialization process, the pollution problem in mining areas has become increasingly serious, posing a huge threat to human health and the ecological environment. In the process of ore mining, smelting and processing, humans will produce various types of wastes, which contain a variety of pollutants such as heavy metals, organic matter and inorganic salts. Under specific environmental conditions, these substances have the possibility of reacting and combining with each other, thereby generating a large number of complex composite pollutants with various types and complex properties. Therefore, the development of a physical and chemical treatment and resource recovery process for composite pollutants in mines has important practical significance and application value.

[0003] Heavy metals can react with coexisting organic ligands, such as ethylenediaminetetraacetic acid (EDTA), citric acid, and oxalic acid in industrial wastewater, to form stable metal-organic complexes. This complexation enhances the stability and solubility of metal ions in a wide pH range, making it difficult to effectively treat them through conventional strategies such as membrane separation, adsorption, and precipitation, because these strategies cannot efficiently break the heavy metal complexes and recover the free heavy metal ions.

[0004] Electrochemical treatment of heavy metal complexes in wastewater is an ideal method. It has the advantages of simple operation, strong controllability, economic applicability, mild reaction conditions, little environmental impact, and no secondary pollution, and has long been favored by researchers. The advanced oxidation process of peroxodisulfate (PDS) is a feasible method in the field of wastewater treatment. Reasonable catalyst anode materials can activate PDS to produce more ROS, thereby improving the efficiency of treatment.

[0005] Based on the above situation, it is urgent to develop ideal anode materials suitable for electrochemical processes, so as to promote the widespread and efficient application of electrochemical processes in treating underground wastewater pollutants. Summary of the invention

[0006] In view of the needs and existing problems in the above-mentioned fields, the present invention has conducted research and development on the treatment of composite pollutants in groundwater by carbon dioxide polymers. Based on the research results, the present invention is proposed, which is as follows: A first aspect of the present invention provides a method for preparing a new material for treating composite pollutants in mining areas by electrochemical process, characterized in that it comprises the following steps: (1) Add malonic acid, acetic anhydride, ammonium molybdate and ferric sulfate into a reaction vessel, mix and heat to dissolve, and continue to raise the temperature to 135-145°C and maintain for 3-6 hours; (2) After the reaction is completed, add ether dropwise to precipitate the product, filter it with suction, then wash it with ether and collect the precipitated product; (3) The precipitated product is vacuum dried to obtain a solid product; (4) The solid product is heated to 300° C. in a nitrogen atmosphere, heat treated at this temperature for 0.5 to 2 hours, and cooled to room temperature to obtain a dark red solid material, namely, an iron-molybdenum-modified carbon dioxide polymer, i.e., the new material.

[0007] Preferably, the preparation method is characterized in that: in step (1), the molar ratio of malonic acid to acetic anhydride is 1:2, the mass fraction of molybdenum is 1.2%, the mass fraction of iron is 1.3%, the heating and dissolving temperature is 90°C, and the heating time is 15 minutes.

[0008] Preferably, the preparation method is characterized in that: in step (4), the heating rate in the nitrogen atmosphere is 5°C / min.

[0009] Preferably, the preparation method is characterized in that: in step (4), it also includes grinding after the heat treatment and storing it in a dry sampling bottle.

[0010] The second aspect of the present invention seeks protection for a new material prepared by any of the above methods.

[0011] The third aspect of the present invention seeks protection for an electrochemical electrode, characterized in that the surface material of the electrode is coated with the above-mentioned new material.

[0012] Preferably, the electrochemical electrode is characterized in that the loading amount of the new material is 0.3-1.0 mg / cm 2 The loading capacity of the new material is 0.6 mg / cm 2 .

[0013] The fourth aspect of the present invention is to protect an electrochemical degradation process for treating composite pollutants in groundwater in mining areas, characterized in that the composite pollutants in groundwater refer to wastewater contaminated by heavy metal complexes in mining areas, containing one or more of Mn, Cr, Cu, Zn, As, Cd, Sb, and Pb; The electrochemical degradation process comprises the following steps: (1) configuring an electrochemical degradation cell, wherein the anode electrode is any of the above-mentioned electrochemical electrodes; (2) Preparing an electrolyte: Take the wastewater contaminated by heavy metal complexes in the mining area to be treated, add peroxodisulfate and sodium sulfate to prepare an electrolyte; (3) Turn on the power to start the reaction.

[0014] Preferably, the electrochemical degradation process is characterized in that the current in step (3) is 7.5 mA / cm² and the reaction time is 30 to 120 minutes.

[0015] Preferably, the electrochemical degradation process is characterized in that the wastewater contains one or more of Mn, Cr, Cu, Zn, As, Cd, Sb, and Pb.

[0016] Preferably, the electrochemical degradation process is characterized in that the final concentration of peroxodisulfate in the electrolyte is 5 mM, and the final concentration of sodium sulfate is 50 mM.

[0017] Beneficial effects of the present invention The carbon dioxide polymer p(C3O2)x is a highly conjugated material formed by the spontaneous polymerization of carbon monoxide (C3O2) at low temperatures. Its oxygen-rich framework gives it good acid resistance and good structural stability. In addition, its synthesis conditions are relatively mild and it is soluble in solvents. The inventors speculate that the above characteristics of the carbon dioxide polymer make it an excellent candidate material. Its oxygen-rich carbon framework may provide abundant adsorption or reaction sites, which is easy to prepare on a large scale and can be coated on a carrier for water treatment. Based on the above speculation, the inventors developed a molybdenum-modified carbon dioxide polymer (Mo-p(C3O2)x-300) suitable for efficient electrochemical wastewater treatment processes, and studied its application in groundwater treatment.

[0018] In the Fe / Mo modified tricarbon dioxide polymer provided by the present invention, molybdenum has the effect of adsorbing or catalyzing the conversion of heavy metal ions and organic pollutants, and its oxygen-rich carbon framework may also provide additional adsorption or reaction sites. The electron-rich Fe site can effectively donate electrons for PDS reduction, thereby generating more free radicals to attack complex pollutants. In addition, the low-valent Mo species has a strong reducing ability and can convert Fe 3+ Reduction to Fe 2+ , thereby realizing the cycle of Fe, further prompting the oxidant to generate more free radicals to break the complex pollutants. Moreover, under certain conditions, Mo will be converted into MoO4 2- , and then precipitate with heavy metal ions in the solution to form insoluble heavy metal molybdate precipitates, thereby achieving effective removal of heavy metal ions. This process can achieve the purpose of removing heavy metal ions without the need for additional chemical precipitants, significantly reducing the cost of wastewater treatment.

[0019] The data from exemplary embodiments show that the Fe / Mo modified tricarbon dioxide polymer developed by the present invention, when used as an anode coating material, can achieve a removal efficiency of 100% for heavy metals in complex pollutants within 45 minutes in the electrochemical degradation process. When treating mine groundwater for 120 minutes, the removal efficiency is 80.1%. It is widely used in the treatment of complex pollutants in mining areas and has great environmental and economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Fe / Mo-p(C3O2) prepared in Example 1 of the present invention x SEM and corresponding mapping diagram.

[0021] Figure 2 Fe / Mo-p(C3O2) prepared in Example 1 of the present invention x -300 SEM and corresponding mapping diagram.

[0022] Figure 3 Fe / Mo-p(C3O2) provided by the present invention x -300 test results of removing metal-organic complexes through electrochemical degradation process, where the vertical axis C / C0 represents the Pb-EDTA removal ratio; the horizontal axis represents the treatment time.

[0023] Figure 4 Fe / Mo-p(C3O2) provided by the present invention x -300 test results of removing heavy metals from underground mine wastewater through electrochemical degradation process, where the vertical axis represents the lead concentration in groundwater; the horizontal axis represents the treatment time. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0025] Example 1 Preparation of Fe / Mo modified carbon dioxide polymer of the present invention The preparation of the Fe and Mo modified carbon dioxide polymer of the present invention is carried out according to the following steps: 1. Mix malonic acid and acetic anhydride in a molar ratio of 1:2, and add ammonium molybdate and ferric sulfate so that the mass fraction of molybdenum in the mixture is 1.2% and the mass fraction of iron is 1.3%. Heat the mixture to 90°C and keep it for 15 minutes.

[0026] 2. Then the temperature was raised to 140°C and maintained for 5 hours. Ether was slowly dripped into the flask to precipitate the product until the precipitation was complete. The solid product was collected by suction filtration and washed three times with ether.

[0027] 3. The product was placed in a vacuum oven and dried overnight to obtain a solid product, represented by Fe / Mo-p(C3O2)x.

[0028] 4. Transfer 1 g of Fe / Mo-p(C3O2)x to a porcelain boat, heat it at a heating rate of 5°C / min in a nitrogen atmosphere and heat treat it at 300°C for 1 hour. After cooling to room temperature, collect the solid product Fe / Mo modified tricarbon dioxide polymer, denoted as Fe / Mo-p(C3O2)x-300, and grind the solid product until it passes through a 200-mesh sieve for later use.

[0029] The calcined Fe / Mo-p(C3O2)x-300 can avoid or reduce the dissolution of catalyst Mo during sewage treatment.

[0030] 5. Product testing and characterization: The solid products Fe / Mo-p(C3O2)x and Fe / Mo-p(C3O2)x-300 obtained in steps 3 and 4 were detected by scanning electron microscopy (SEM) and element distribution mapping.

[0031] The results are as follows Figure 1 and Figure 2 As shown, the element distribution mapping results prove that the solid products Fe / Mo-p(C3O2)x and Fe / Mo-p(C3O2)x-300 obtained by the present invention are composed of four elements: Fe, Mo, C, and O. At the same time, scanning electron microscopy detection shows that ( Figure 1 Upper left and Figure 2 (Upper left) There are significant differences in morphology between Fe / Mo-p(C3O2)x and Fe / Mo-p(C3O2)x-300.

[0032] Example 2 Performance test of the Fe / Mo modified carbon dioxide polymer of the invention The Fe / Mo-p(C3O2)x-300 modified carbon dioxide polymer of Example 1 of the present invention was heated to 0.6 mg / cm 2 The loading ratio was drop-coated on the anode carbon felt, and an electrochemical constant current test was carried out in the electrolyte (0.0278g of lead chloride and 0.0372g of disodium ethylenediaminetetraacetic acid dihydrate were weighed in a 1L volumetric flask, and 1000ml of ultrapure water was added and stirred to dissolve, i.e., containing 65mg / L Pb-EDTA; 5mM peroxodisulfate, and 50mM sodium sulfate).

[0033] The specific steps are as follows: Step 1 Pretreatment of carbon felt: Cut the carbon felt into 1×2cm 2, immersed in nitric acid for 6 h, then ultrasonically treated with acetone, ethanol and deionized water for 30 min respectively, and dried at 70 °C for 12 h Step 2 Preparation of working electrode 5 mg of Fe / Mo-p(C3O2) x -300 was dispersed in a solution obtained by mixing 0.3 mL of water, 0.7 mL of ethanol and 0.02 mL of Nafion 117, and treated under ultrasonication for 30 minutes to obtain a catalyst solution.

[0034] The catalyst solution is dropped onto the carbon felt, and Fe / Mo-p(C3O2) on the carbon felt x -3000 has a loading of 0.6 mg / cm 2 . Step 3: Construction of the reaction device Fe / Mo-p(C3O2) x -300 carbon felt is used as the working electrode, and the other carbon felt is connected to the counter electrode; Take 80ml of the above electrolyte and add it to a 100ml electrolytic cell to start the reaction. Set the current to 7.5mA / cm 2 , reaction time 1.5h.

[0035] Step 4: Reaction detection At regular intervals, the supernatant was taken out by syringe and filtered through a microporous filter membrane, and the content of residual Pb-EDTA in the sample was determined by liquid chromatography. After the reaction was completed, a small amount of solution was taken for atomic absorption testing of the concentration of residual lead ions.

[0036] The removal effect of the Fe / Mo modified tricarbon dioxide polymer provided by the present invention on Pb-EDTA is as follows: Figure 3 As shown, the vertical axis C / C0 represents the removal rate (%), and the horizontal axis t / min represents the treatment time. 2 When the loading amount is 2.5, the removal rate of heavy metal-organic complex Pb-EDTA with a concentration of 65 mg / L reaches 100% within 45 minutes.

[0037] Example 3 Practical application demonstration of actual mine underground wastewater Step 1 Pretreatment of wastewater to be treated 1. Collect samples: Collect representative wastewater samples from the mine’s underground wastewater discharge outlet or contaminated area to ensure that the samples can accurately reflect the pollution status of the mine’s underground wastewater.

[0038] 2. Preliminary analysis: Conduct preliminary analysis on the collected wastewater samples to determine the content of heavy metals, COD value, pH value and other basic parameters in order to understand the pollution degree and characteristics of the wastewater. The measurement data are as follows

[0039] 3. Filtration: If there are a lot of suspended solids in the wastewater sample, you can first filter it with filter paper or microporous filter membrane to remove large particles of suspended solids; Step 2 Preparation of working electrode 1. Carbon felt pretreatment: Cut the carbon felt into 1×2cm² and soak it in nitric acid for 6 hours to remove impurities and oil stains on the surface of the carbon felt. Then, ultrasonically treat it with acetone, ethanol and deionized water for 30 minutes respectively to further clean the carbon felt, and finally dry it at 70℃ for 12 hours.

[0040] 2. Catalyst solution preparation: 5 mg of Fe / Mo-p(C3O2) x -300 is dispersed in 0.3 mL of water, 0.7 mL of ethanol and 0.02 mL of Nafion 117 solution (or expanded according to this ratio), and the mixed solution is treated under ultrasonication for 30 minutes to obtain a uniform catalyst solution.

[0041] 3. Catalyst drop coating: Take the catalyst solution and evenly drop it on the pretreated carbon felt to ensure that the catalyst coating area is 1×1 cm². Then place the drop-coated carbon felt in a drying oven and dry it at 60°C for 30 minutes to make the catalyst firmly adhere to the surface of the carbon felt to obtain a working electrode.

[0042] Step 3: Construction of the reaction device 1. Electrode preparation: The working electrode prepared in step 2 and coated with the catalyst is used as the anode, and another piece of carbon felt without the catalyst coated is used as the cathode.

[0043] 2. Electrolytic cell assembly: Select an electrolytic cell of appropriate specifications, place the anode and cathode in parallel in the same chamber of the electrolytic cell, and keep 2 cm between the two electrodes to ensure the smooth progress of the electrochemical reaction.

[0044] 3. Electrolyte preparation: Take underground mine wastewater to prepare electrolyte, and the initial lead concentration is measured to be 25 mg / L. Peroxodisulfate and sodium sulfate are added to make the final concentration of peroxodisulfate in the electrolyte 5 mM and the final concentration of sodium sulfate 50 mM; Step 4: Reaction detection 1. Start the reaction: Connect the power supply, apply a constant current of 7.5 mA / cm² to the electrolytic cell, and record the time when the reaction starts.

[0045] 2. Regular sampling: Use a syringe to extract a certain amount of supernatant from the electrolytic cell at regular intervals, filter it through a 0.22μm microporous filter membrane, and collect the filtrate for subsequent analysis and testing.

[0046] 3. Analysis and detection: The concentration of residual heavy metal ions in the filtrate is measured by atomic absorption spectrometer. The test data is as follows: Figure 4 As shown, the initial lead concentration was 22.6 mg / L, which could be reduced to a minimum of 4.34 mg / L after 120 minutes of treatment, with a removal efficiency of 80.1%.

[0047] The above exemplary implementation data show that the new material Fe / Mo-p(C3O2) provided by the present invention x -300 is an excellent candidate material for removing heavy metals from complex pollutants through electrochemical degradation process and has wide application value.

Claims

1. A method for preparing a new material for treating composite pollutants in mining areas by electrochemical process, characterized in that: The following steps are involved: (1) Add malonic acid, acetic anhydride, ammonium molybdate and ferric sulfate into a reaction vessel, mix and heat to dissolve, and continue to raise the temperature to 135-145°C and maintain for 3-6 hours; (2) After the reaction is completed, add ether dropwise to precipitate the product, filter it with suction, then wash it with ether and collect the precipitated product; (3) The precipitated product is vacuum dried to obtain a solid product; (4) The solid product is heated to 300° C. in a nitrogen atmosphere, heat treated at this temperature for 0.5 to 2 hours, and cooled to room temperature to obtain a dark red solid material, namely, an iron-molybdenum-modified carbon dioxide polymer, i.e., the new material.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of malonic acid to acetic anhydride is 1:2, the mass fraction of molybdenum is 1.2%, the mass fraction of iron is 1.3%, the heating and dissolving temperature is 90°C, and the heating time is 15 minutes.

3. The preparation method according to claim 1, characterized in that: In step (4), the heating rate in the nitrogen atmosphere is 5°C / min.

4. The preparation method according to claim 1, characterized in that: Step (4) further includes grinding after the heat treatment and storing the mixture in a dry sample bottle.

5. A new material prepared by the preparation method according to any one of claims 1 to 4.

6. An electrochemical electrode, characterized in that The surface material of the electrode is coated with the new material described in claim 5.

7. The electrochemical electrode according to claim 6, characterized in that The coating amount of the new material is 0.3-1.0 mg / cm 2 .

8. An electrochemical degradation process for treating composite pollutants in groundwater in mining areas, characterized in that: The groundwater composite pollutants refer to wastewater contaminated by heavy metal composites in mining areas, containing one or more of Mn, Cr, Cu, Zn, As, Cd, Sb, and Pb; The electrochemical degradation process comprises the following steps: (1) An electrochemical degradation cell is provided, wherein the electrochemical electrode according to claim 6 or 7 is used as an anode electrode; (2) Preparing an electrolyte: Take the wastewater contaminated by heavy metal complexes in the mining area to be treated, add peroxodisulfate and sodium sulfate to prepare an electrolyte; (3) Turn on the power to start the reaction.

9. The electrochemical degradation process according to claim 8, characterized in that: The current applied in step (3) is 7.5 mA / cm²; the reaction time is 30 to 120 minutes.

10. The electrochemical degradation process according to claim 8, characterized in that: The final concentration of peroxodisulfate in the electrolyte was 5 mM, and the final concentration of sodium sulfate was 50 mM.

Citation Information

Patent Citations

  • Preparation method of iron-molybdenum bimetal MOF derivative catalyst and application of iron-molybdenum bimetal MOF derivative catalyst in wastewater treatment

    CN116943673A